Experimental evidence for optimal hedgerow cutting regimes for Brown hairstreak butterflies. Issue 2 (10th June 2017) - Staley, Joanna T.; Botham, Marc S.; Amy, Sam R.; Hulmes, Sarah; Pywell, Richard F.
Abstract: The Brown hairstreak butterfly has declined in range and abundance over the past 50 years, leading to designated conservation status in several European countries including England and Wales. The Brown hairstreak's decline has been linked to changes in hedgerow management, based on mortality of eggs over winter and female oviposition preferences. We assessed Brown hairstreak egg abundance in late winter over 4 years in response to hedgerow management treatments to manipulate the frequency, timing, and the intensity of trimming (reduced intensity resulting in an annual increase of approximately 10 cm in hedge height and width), using a field experiment with a randomised block design. Hedgerow plots cut every year to a standard height and width had the lowest Brown hairstreak egg abundance; this is the most common hedgerow management outside agri‐environment schemes (AES). Cutting hedgerow plots at a reduced intensity nearly doubled the number of surviving eggs in late winter. Plots cut at a reduced frequency in autumn (once every 3 years), which forms part of current English AES, had 1.3 times more eggs than those cut annually. Current AES management prescriptions are likely to benefit the Brown hairstreak, but its requirements need to be balanced with those of other taxa in relation to the timing of hedgerow cutting. Cutting hedges at a reduced intensity has previously been shown to benefit the wider Lepidoptera community as well as Brown hairstreak butterflies. Reduced intensity cutting does not currently form part of AES hedgerow prescriptions, but could be considered for inclusion in future schemes.